Mediastinitis and pericarditis after endobronchial ultrasound‐guided transbronchial needle aspiration. Issue 1 (24th December 2014) - Fukunaga, Kentaro; Kawashima, Satoru; Seto, Ruriko; Nakagawa, Hiroaki; Yamaguchi, Masafumi; Nakano, Yasutaka
Abstract A 73‐year‐old man was admitted to our hospital for further investigation of multiple lung nodules and lymphadenopathy that were observed on chest radiography. Endobronchial ultrasound‐guided transbronchial needle aspiration (EBUS‐TBNA) was performed to sample the lower paratracheal lymph node (4R), leading to a definitive diagnosis of squamous cell carcinoma of the lung. About 2 weeks after EBUS‐TBNA, the patient had a high temperature, anterior chest pain, tachycardia, and hypotension. The diagnosis of infectious mediastinitis and pericarditis as complications of EBUS‐TBNA, which were successfully treated with systemic antibiotics, was made after examinations. EBUS‐TBNA is minimally invasive and useful for the diagnosis of hilar and mediastinum lesions particularly in determining the extent of lung cancer. With the increased employment of this method, critical complications may also increase. Clinicians should be aware of the rare but critical complications associated with EBUS‐TBNA.